Potential Application of Circulating Tumor Cell Markers to Evaluate Response to Chemotherapy in Breast Cancer Patients: A Narrative Review - Wibisana, I Gusti Ngurah Gunawan (Proceedings Book of International Conference and Exhibition on The Indonesian Medical Education Research Institute, 2024)
Breast cancer treatment has shifted from conventional therapy to personalized medicine based on heterogeneous and dynamic cancer biology characteristics. Cancer cells can actively spread from the primary tumor into the peripheral circulation as circulating tumor cells (CTC) to initiate cancer progression. The liquid biopsy technique, which includes repeated assessment of the number and molecular profile of CTCs, can be used to detect changes in CTC biological behavior, determine chemotherapy resistance, and predict recurrence at the molecular level. Only 3% of the CTC population, in the form of proliferating CTCs, survive and continue the metastatic process as a result of the immune system, biophysical factors, and chemotherapy. These viable CTCs can be identified through 7-Amino Actinomycin D labels, which bind to DNA in the nucleus. These CTCs have the property of cancer stemness and plasticity through the presentation of epithelial and mesenchymal markers due to the epithelial-mesenchymal transition (EMT) process, which enables CTCs to escape the immune system by expressing PD-L1 as immune checkpoint surface signals. When CTCs are still in circulation, they express MUC1, which binds to endothelium and initiates the metastatic adhesion cascade process. Using a flow cytometry method based on surface and intracellular protein markers, these proliferating CTCs can be identified using a label-dependent approach. The response to chemotherapy can be assessed by analyzing information on the changes in the number and characteristics of breast cancer CTCs based on a combination of EMT, immunological checkpoints, cancer stem cells, cell viability, and endothelial adhesion marker protein.